PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN MANGROVE DI DESA SUNGAI KUPAH KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Ningsih, Rahayu Setya; Roslinda, Emi; Astiani, Dwi (JURNAL HUTAN LESTARI, 2020)
People’s perception on mangrove forest is one form of mangrove responses concerning the function and benefits of mangrove ecosystems including physical, biological, chemical, economic and social benefits. One of example mangrove forests  is  Sungai Kupah village, Sungai Kakap subdistrict, Kubu Raya district. This study aims to understand people’s perceptions of the mangrove forests in the Sungai Kupah village and to understand the relationship between perceptions of the individual factors of age, education, knowledge, cosmopolitan levels, income levels, and dependability. The research uses the survey method and analyzed with Kendall tau’s correlation and descriptive analysis. People’s perception on mangrove forests in the Sungai Kupah village it’s positively inclined, which is 51,14%. Knowledge factor have a significant positive correlation; Education, income, cosmopolitan and dependency factors are low in their positive correlations; While age and distance factors tend have a negative insignificant correlation with people’s perception of mangrove forests in the village of the Sungai Kupah. The perception can be used as a reference to bringing communities into further mangrove.Keywords : Communities, individual factors, mangrove forests, perception, qualitative data